The conception of disease: a historical, philosophical, anthropological, epistemiological and political approa - Pinheiro, Josefa Nunes; Chaves, Mônica Campos; Jorge, Maria Salete Bessa (Rev Rene, 2004)
This article presents reviews by authors on the concept of disease, based upon a theoretical-explicative approach used to assess the most recurrent ideas involved in the understanding of this phenomenon. The text broaches historical, cultural, political and epistemological aspects of the concept of disease. This paper intends to contribute to the deepening of the interface between biomedical and social sciences. Therefore, we concluded that, for a better understanding of a disease, we ought to take into account its plural character and its historical and sociological construction.